Relationship of chronological age and sexual maturity with skeletal maturity by magnetic resonance imaging of the distal radial epiphysis in adolescent football players - Bolivar, J.; Sandoval, O.; Osorio, J.; Dib, G.; Gallo, J. (Apunts Medicina de l'Esport, 2015)
Although the grade of fusion of the left distal radial epiphysis (LDRE) observed by magnetic resonance imaging (MRI) has been linked to chronological age (CA), its relationship to Tanner stage of the genitals in the Latin American population is unknown.